Ethnomathematics of Baitu Usyaqil Quran (BUQ) Mosque and Pesantren Darussalam, Banyumas Regency - Kusno Kusno; Eka Setyaningsih; Anggun Badu Kusuma (AlphaMath : Journal of Mathematics Education, 2022)
The mosque is the oldest Islamic culture which is the centre of civilization for Muslims for every group, both adults and children. However, so far the mosque environment is rarely used as an effective learning resource to explore more contextual, meaningful and educational mathematics material. The purpose of this study was to explore mathematics teaching materials and religious values from objects (artefacts) around the mosque. The artefacts explored are mosque objects that have religious values, namely prayer rugs, prayer rugs, mosque reliefs and covers of the Qur'anic manuscripts. The research location is in the Baitu Usyaqil Quran (BUQ) Mosque and the Pesantren Darussalam Purwokerto Mosque, Banyumas, Central Java. The data collection method uses observation, documents and a literature review. The data analysis technique used descriptive qualitative analysis. The results showed that, prayer rugs, prayer rugs, mosque reliefs and covers of the Qur'anic manuscripts contain various transformational geometry concepts such as symmetry, reflection, translation, rotation, and dilation. The results of this study are very important for developing a mathematics curriculum based on student culture.